2022
DOI: 10.1002/jgt.22848
|View full text |Cite
|
Sign up to set email alerts
|

Between proper and strong edge‐colorings of subcubic graphs

Abstract: In a proper edge-coloring the edges of every color form a matching. A matching is induced if the end-vertices of its edges induce a matching. A strong edge-coloring is an edge-coloring in which the edges of every color form an induced matching. We consider intermediate types of edge-colorings, where edges of some colors are allowed to form matchings, and the remaining form induced matchings. Our research is motivated by the conjecture proposed in a recent paper of Gastineau and Togni on S-packing edge-coloring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In addition, Gastineau and Togni in [13] showed that every subcubic graph G $G$ with a 2‐factor has a (12,25) $({1}^{2},{2}^{5})$‐packing edge‐coloring, and if the graph is additionally 3‐edge‐colorable, then it is (12,24) $({1}^{2},{2}^{4})$‐packing edge‐colorable. Hocquard et al [14, 15] were able to show the same holds without the assumption of a 2‐factor. They also restate the following conjectures of Gastineau and Togni.…”
Section: Further Researchmentioning
confidence: 76%
See 4 more Smart Citations
“…In addition, Gastineau and Togni in [13] showed that every subcubic graph G $G$ with a 2‐factor has a (12,25) $({1}^{2},{2}^{5})$‐packing edge‐coloring, and if the graph is additionally 3‐edge‐colorable, then it is (12,24) $({1}^{2},{2}^{4})$‐packing edge‐colorable. Hocquard et al [14, 15] were able to show the same holds without the assumption of a 2‐factor. They also restate the following conjectures of Gastineau and Togni.…”
Section: Further Researchmentioning
confidence: 76%
“…2 5 -packing edge-coloring, and if the graph is additionally 3-edge-colorable, then it is (1 , 2 ) 2 4 -packing edge-colorable. Hocquard et al [14,15] were able to show the same holds without the assumption of a 2-factor. They also restate the following conjectures of Gastineau and Togni.…”
mentioning
confidence: 75%
See 3 more Smart Citations